FAKTOR YANG BERPENGARUH TERHADAP KEBERHASILAN DALAM PEMBERIAN ASI EKSKLUSIF DI DESA HAMPARAN PERAK KEC. HAMPARAN PERAK KAB. DELI SERDANG - Lubis, Desi Handayani (Universitas Negeri Medan, 2018)
ABSTRACTThis study aims to determine the factors that influence the success of exclusive breastfeeding. The design of this study is descriptive analytic with a sample size of 26 respondents with a total sampling method. The results of this study the majority of respondents aged 26-30 years as many as 10 people (38.5%), the majority of education secondary education respondents as many as 19 people (73.1%), the majority of respondents as IRT as many as 20 people (76.9%), the majority of respondents earn < 1,000,000 as many as 22 people (84.6%), and the majority of children's parity was 17 (65.4%). From the results of the product moment statistical test it can be concluded that the management factor at the place of delivery that supports breastfeeding and providing breastfeeding facilities in public places is a factor that influences the success of exclusive breastfeeding.Keywords: Factors, Success, Exclusive Breastfeeding